Prevalence and factors associated with compassion fatigue, compassion satisfaction, burnout in health professionals. Issue 2 (21st March 2022) - Kartsonaki, Maria George; Georgopoulos, Dimitris; Kondili, Eumorfia; Nieri, Alexandra Stavroula; Alevizaki, Afroditi; Nyktari, Vasileia; Papaioannou, Alexandra
Abstract: Background: Constant exposure of health professionals to the pain and suffering of patients can adversely affect their emotional wellbeing. Aim: The study aimed to investigate the prevalence and the factors affecting the levels of secondary traumatic stress/compassion fatigue (STS/CF), burnout (BO) and compassion satisfaction (CS) of health professionals working in adult and paediatric Intensive Care Units (ICU) as well as in departments treating patients with serious illness in five hospitals in Crete. Study Design: A descriptive cross‐sectional survey with the use of the Professional Quality of Life Scale (ProQOL‐CSF‐R‐IV) questionnaire. Methods: We enrolled medical, nursing and support staff working in the adult and paediatric ICU, emergency, oncology, haematology and neurosurgical departments, haemodialysis unit and operating theatre. Results: 598 health professionals completed the questionnaire (response rate 73.2%). Significantly increased levels of STS/CF were observed in non – ICU as compared to ICU staff ( p  = .009) females compared to males ( p  < .001), those who have previously experienced a traumatic event ( p  < .004), nurses and support staff compared to doctors ( p  = .007 and p  = .028 respectively), and people not working in a department by choice ( p  < .001). CS was higher for older professionals, personnel subjected to stress reduction techniques ( p  < .019) and professionals working with children or mixed adults and children population ( p  = .009). Rolling schedule and bad working conditions negatively affected CS ( p  = .02, p  = .001). Increased BO levels were associated with younger age ( p  = .029) and showed a positive correlation with STS/CF ( r  = .356, p  < .001). Conclusions: STS/CF is common in health professionals regardless of their profession, working department or hospital level. Non‐ICU staff displayed higher STS/CF levels. Working in a department by choice ameliorates CS, BO and STS/CF. Relevance to Clinical Practice: Health professionals need to be informed about the risks of projecting patients' suffering on themselves. Hospital managers and department heads are responsible to provide appropriate support.